Quality of raw milk type C and refrigerated in traditional dairy systems of southwest Goiás, Brazil - Melo, Aurélio Ferreira (2013)
The aim of the study was to evaluate the quality of raw milk refrigerated and raw type C of dairy systems low-tech of Southwest Goiás, Brazil, and ensure that the milk produced meets the requirements of normative instruction 62/2011. It was collected 49 samples of raw milk refrigerated and raw milk type C under aseptic conditions, using flask of 40 ml containing preservative azidiol ® for analysis of TBC and Bronopol® for determination of SCC and chemical composition. The analyzes were performed at the Laboratory of Quality Milk Research Center of Food School of Veterinary Medicine and Animal Science of the Federal University of Goiás to compare means between treatments we used the Tukey test at 5% probability. The results of fat and SCC showed a higher incidence of mastitis in milk refrigerated is directly related to the increase in the fat content of the milk. The total bacterial count of milk type C and refrigerated were higher than the limit established by Brazilian legislation of milk quality, and indicated the need for greater attention to hygiene during the collection and storage of milk.